Conformation of lithium-aluminium alloy interphase-layer on lithium metal anode used for solid state batteries. (1st July 2018) - Zhong, Hai; Sang, Lin; Ding, Fei; Song, Jiangxuan; Mai, Yaohua
Abstract: The effects of an Li-Al layer on the modified-Li anode based on solid state batteries are studied. The structure, surface morphology, and cyclic stability of the modified-Li anode are examined by X-ray diffraction spectroscopy, scanning electron microscopy, and electrochemical tests. Results show that interphase layer can prevent Li from reacting with Li1.5 Al0.5 Ge1.5 (PO4 )3 and displays a much better cycling stability compared with the bare-Li anode used in symmetric cells. The assembled solid state batteries with modified-Li anode and LiMn0.8 Fe0.2 PO4 cathode can deliver an initial discharge capacity of 153 mAh g −1 with good cyclic stability and rate performance at 50 °C. The reason for this is that the Li-Al alloy interphase layer can prevent localised Li enrichment, then suppress lithium dendrite growth, and the Li-Al layer on the anode possesses good stability in the presence of Li1.5 Al0.5 Ge1.5 (PO4 )3 powder and better interphase contact results between the anode and solid electrolyte in solid state batteries.